2015
DOI: 10.5937/ffr1502163p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of synbiotic on growth and antioxidant status of blood in broiler chicken

Abstract: In the present study, the impact of synbiotic, compared to control treatment (CON), on growth performance and antioxidative status of broilers blood was investigated. The experiment was carried out on a total of 500 one-day-old broiler chickens of both sexes. The broilers were divided into two treatments with five replicates, based on a completely randomized design. The control treatment was fed basal diet, while experimental treatment was supplemented with synbiotic in addition of 1 g/kg of feed (SYN) in fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…This was particularly evident in turkeys receiving the probiotic (Bacillus licheniformis and Bacillus subtilis) together with Yarrowia lipolytica or Saccharomyces cerevisiae yeast. These results correspond to findings by Popović et al [28], who observed a significant reduction in MDA in the blood of chickens receiving feed supplemented with a probiotic in combination with a prebiotic (synbiotic). According to Li et al [29], supplementing poultry feed with mannan oligosaccharides and β-glucans reduces accumulation of the lipid oxidation end product (MDA) in the tissues of broiler chickens and improves the oxidative status of weaned piglets [30].…”
Section: Discussionsupporting
confidence: 91%
“…This was particularly evident in turkeys receiving the probiotic (Bacillus licheniformis and Bacillus subtilis) together with Yarrowia lipolytica or Saccharomyces cerevisiae yeast. These results correspond to findings by Popović et al [28], who observed a significant reduction in MDA in the blood of chickens receiving feed supplemented with a probiotic in combination with a prebiotic (synbiotic). According to Li et al [29], supplementing poultry feed with mannan oligosaccharides and β-glucans reduces accumulation of the lipid oxidation end product (MDA) in the tissues of broiler chickens and improves the oxidative status of weaned piglets [30].…”
Section: Discussionsupporting
confidence: 91%
“…The present findings manifested the physiological role of probiotics to enhance Japanese quail's antioxidant system because its ability to produce certain substances captures reactive oxygen species, scavenge free radicals, and inhibit their cytotoxic activity ( Lin and Yen, 1999 ). The findings of Aluwong et al, 2013b , Popović et al, 2015 , Abudabos et al, 2016 are in close agreement with our results.…”
Section: Discussionsupporting
confidence: 92%
“…MDA may be responsible for DNA fragmentation, cell memebrane strucrure destruction, cross-linking and apoptosis. The estrimation of GPx and SOD acitivity and MDA content gives the oxygen free radical level ( 45 ). Dietary effective ingredients such as some herbs, synthetic antioxidants, prebiotics, probiotics, and synbiotics are known to elevate the level of antioxidant enzymes that get rid of the free radicals in the body ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study also indicated that the highest liver antioxidant status was observed in broilers supplemented with FOS prebiotic. The results of this study revealed that using FOS in the diet of the broiler chickens induced antioxidant reactions in blood and livers, indicated by antioxidant enzyme action.Similarly, ( 45 ) et al studied the effect of a synbiotic on antioxidative status of broiler blood. Their results showed a significant reduction in MDA concentration in comparison to control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation